Mussel-Inspired Recombinant Adhesive Protein-Based Functionalization for Consistent and Effective Antimicrobial Treatment in Chronic Inflammatory Skin Diseases - Kim, Suhyeon; Kim, Nam Hyeong; Khaleel, Zinah Hilal; Sa, Deok Hyang; Choi, Daekyu; Ga, Seongmin; Kim, Chang Geon; Jang, Jiye; Kim, Kyeonghyun; Kim, Ye Ji; Chang, Sukkum Ngullie; Park, Seon Min; et al. (Wiley Blackwell, 2024)
Chronic inflammatory skin diseases, characterized by a vicious cycle of infection and hyperinflammation, necessitate consistent and effective antimicrobial treatment of target lesions to achieve practical therapeutic outcomes. Antimicrobial dressing materials offer notable advantages over conventional therapeutic drugs, including ease of application, extended contact time, and targeted antimicrobial action, resulting in enhanced efficacy in breaking the vicious cycle. In line with these advantages, this study aims to develop a plug-and-playable recombinant adhesive protein (RAP) inspired by the adhesive properties of marine mussels, serving as a durable and effective surface functionalization strategy. By genetically recombining mussel foot protein with antimicrobial peptides, RAP effectively incorporates antimicrobial properties into biomaterials for treating chronic inflammatory skin diseases. The durable adhesion of RAP ensures long-lasting antimicrobial functionality on target surfaces, MFP making it a promising approach to inhibit chronic inflammation. In addition, when dip-coated onto cotton gauze, RAP can be utilized as an antimicrobial patch, effectively suppressing chronic inflammation through the inhibition of bacteria-induced toll-like receptor signaling. These findings underscore the potential of nature-inspired protein-based surface functionalization of biomaterials as a compelling approach to advance the treatment of chronic inflammatory skin diseases. Mussel-inspired plug-and-playable recombinant adhesive protein (RAP) is developed to incorporate an antimicrobial function to biomedical materials for the treatment of chronic inflammatory skin. RAP not only shows an immediate antimicrobial activity but also enables a highly durable adhesion on the surface, resulting in a suppression of chronic inflammatory skin in an antimicrobial-induced anti-inflammation manner.image